Indonesia : Financial System Stability Assessment-Press Release and Statement by the Executive Director for Indonesia. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This paper assesses the stability of Indonesia's financial system. Since the 2010 Financial Sector Assessment Program, Indonesia's macroeconomic performance has been robust and the financial system has been stable. Systemic risk is low and the banking system appears generally resilient to severe shocks. Market-based indicators point to relatively low levels of systemic risk. Under severe stress-test scenarios, banks experience sizable credit losses, particularly from corporate exposures, but high capital levels and strong profitability help absorb most of these losses. Many banks face relatively small shortfalls in liquidity stress tests, including in foreign currency, and these appear manageable for Bank Indonesia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet